The Role of Indonesian Police Through “Cyber Patrol” in Preserving and Maintaining Cyber Room Security - Edi Saputra Hasibuan (International Journal of Social Service and Research, 2022)
The development of an increasingly advanced era has an impact on the advancement of technology and information that is increasing rapidly. The era of the Industrial Revolution 4.0 has also become something that requires everyone to be more sensitive and accustomed to using technology. However, like two sides of the same coin, it seems that everything that has a positive impact also has a drawback or a negative impact, the existence of deviations either by system errors or from human resources, causing new problems in the cyber world. Carding crimes, misuse of data, phishing, and defacement of a website, as well as activities that cause unrest, such as defamation and hoaxes, are some disturbing activities in the cyber world. Regarding this problem, the State or Government, which has the responsibility to protect its citizens, has begun to take a stand by coordinating with relevant institutions to take action and prevent the increase of crime in the cyber world. The National Police, as one of the state's tools and the front line in dealing with security and law enforcement, has formed a patrol team called the "Cyber Police" by conducting "Cyber Patrol" activities. It is very interesting to discuss, considering that nowadays, people can use technology to do something that violates the law; therefore, the existence of the Cyber Police is expected to prevent the bad impact of a cyber incident to create a safe and comfortable environment both directly (real), or indirectly (virtual world).